Tunisia : Fifth Review Under the Extended Fund Facility, and Requests for Waivers of Nonobservance and Modification of Performance Criteria and for Rephasing of Access. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses Tunisia's Fifth Review Under the Extended Fund Facility, and Requests for Waivers of Nonobservance and Modification of Performance Criteria, and for Rephasing of Access. This review focuses on stabilizing the economy ahead of the Fall 2019 elections. Civil service wage hikes and a pause in energy price hikes constitute departures from the policies agreed at the Fourth Review. The authorities will adjust their policy mix to correct for these slippages and keep the economy on a stabilization path, while maintaining social cohesion. Structural reforms should focus on enhancing the business climate and improving access to finance to boost private-sector led growth. The appointment of the members of the High Anti-Corruption Authority would help address corruption concerns. Socio-political tensions and deterioration in security are the main risks to the adjustment strategy. Higher oil prices, spillovers from conflicts in the region, a further slowing of EU growth, rising trade tensions, and shifts in investor sentiment could also jeopardize economic stability.